Clinical usefulness of nutraceutics with acetyl-L-carnitine, α-lipoic acid, phosphatidylserine, curcumin, C, E and B-group vitamins in patients awaiting for carpal tunnel release during COVID-19 pandemic: a randomized controlled open label prospective study - D'Orio, Marco; De Vitis, Rocco; Taccardo, Giuseppe; Rocchi, Lorenzo; Ferrari, Federico; Perna, Andrea; Passiatore, Marco (Acta Biomedica Atenei Parmensis, 2023)
Background and aim of the work: Carpal Tunnel Syndrome (CTS) is provoked by the compression of the median nerve, leading to nerve ischemia, endoneural edema, venous congestion, and subsequent metabolic alterations. Conservative treatments could be considered. The present study investigates the efficacy of a specific blend of a 600 mg dietary integrator composed of acetyl-L-carnitine, α-lipoic acid, phosphatidylserine, Curcumin, C, E and B1, B2, B6 and B12 vitamins in patients with mild to moderate CTS. Methods: The present investigation involved the outpatients who were planned to undergo open surgical decompression of the median nerve awaiting surgery from June 2020 and February 2021. CTS surgery has been significantly reduced in our institutions during the COVID-19 pandemic. Patients were randomized into Group A (dietary integration 600 mg twice day for 60 days) and Group B (control group, no drug administration). Clinical and functional improvement was prospectively measured after 60 days Results: One-hundred forty-seven patients completed the study, 69 from group A and 78 from group B. BCTQ was significantly improved with the drug administration, as well as BCTQ symptoms subscale, and the pain. BCTQ function subscale and Michigan Hand Questionnaire was not significantly improved. Ten patients in group A (14.5%) declared that they didn’t need further treatment. No major side effects were noticed. Conclusions: Dietary integration could be considered as an option in patients who could not undergo surgery. Symptoms and pain could improve, but surgery remains the gold standard for recovery of function in mild to moderate CTS.